2016
DOI: 10.1016/bs.vh.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

αKlotho and Chronic Kidney Disease

Abstract: Alpha-Klotho (αKlotho) protein is encoded by the gene, Klotho, and functions as a coreceptor for endocrine fibroblast growth factor-23. The extracellular domain of αKlotho is cleaved by secretases and released into the circulation where it is called soluble αKlotho. Soluble αKlotho in the circulation starts to decline in chronic kidney disease (CKD) stage 2 and urinary αKlotho in even earlier CKD stage 1. Therefore soluble αKlotho is an early and sensitive marker of decline in kidney function. Preclinical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 280 publications
1
28
0
1
Order By: Relevance
“…reported that the prevention of Klotho decline and direct supplementation of soluble Klotho are both associated with attenuated renal fibrosis and slowed chronic kidney disease (CKD) progression 24 . However, the effect of Klotho in DKD needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the prevention of Klotho decline and direct supplementation of soluble Klotho are both associated with attenuated renal fibrosis and slowed chronic kidney disease (CKD) progression 24 . However, the effect of Klotho in DKD needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, uremic cardiomyopathy is characterized by cardiac arrest or sudden death, left ventricular hypertrophy, cardiac fibrosis, congestive heart failure, and so on [4-6]. In addition to traditional risk factors such as smoking, hypertension, diabetes, anemia, and volume overload, Klotho deficiency also plays an important role because soluble Klotho (s-Klotho) is a circulating substance exerting multiple systemic biological actions on distant organs, such as directly protecting cells against a variety of insults including hypoxia, hyperoxia, oxidative stress, and cytotoxic medication and suppressing apoptosis [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…13 Klotho also directly can promote the internalization and degradation of the NaPi2a cotransporter in the renal proximal tubules. 56 Klotho also may be a suppressor of vitamin D signaling, 57,58 because klotho knockout mice can be rescued from a phenotype of soft-tissue calcification by deletion of the CYP27B1 gene. 59 Finally, klotho has myriad pleotropic actions as an inhibitor of apoptosis, fibrosis, and cell senescence, and as an up-regulator of autophagy.…”
Section: Klotho: Function and Regulatorsmentioning
confidence: 99%
“…Renal klotho expression and soluble levels of klotho in the blood and urine are decreased in animals and humans with CKD resulting from a variety of etiologies, including glomerular and tubulointerstitial diseases, diabetic nephropathy, subtotal nephrectomy, and others (reviewed by Neyra and Hu 58 ). Because the kidneys are the primary source of soluble klotho, it is perhaps unsurprising that circulating levels of soluble klotho decrease as CKD progresses.…”
Section: Klotho In Ckdmentioning
confidence: 99%